Intra-Abdominal Hypertension and Its Prognostic Impact on Mortality in Cirrhotic Patients with Ascites: The Role of Paracentesis - Mutlu, Ummu; Ulucecen, Sezen Genc; Iliaz, Raim; Atasoy, Alp; Cavus, Bilger; Ormeci, Asli Ciftcibasi; Akyuz, Filiz; Demir, Kadir; Kaymakoglu, Sabahattin; Besisik, Fatih (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Elevated intra-abdominal pressure (IAP) can lead to intra-abdominal hypertension (IAH) and, in severe cases, abdominal compartment syndrome (ACS) in patients with cirrhosis and ascites. Paracentesis reduces IAP and improves abdominal perfusion. Intra-abdominal hypertension can also trigger acute-on-chronic liver failure (ACLF) in decompensated cirrhosis. This study evaluates the association between IAH and short-term mortality in patients with cirrhosis and ascites. Materials and Methods: This prospective, single-center cohort study included 18 patients (7 females, 11 males; median age: 59) sched uled for therapeutic paracentesis. Intra-abdominal pressure was measured using the bladder technique. Patients were grouped based on initial Chronic Liver Failure Consortium Organ Failure (CLIF-C OF) scores as ACLF or non-ACLF and followed up for 3 months. Results: The median model for end-stage liver disease score was 17 (IQR 11-19). The primary etiologies of cirrhosis were viral hepatitis and alcoholic liver disease. Independent risk factors for IAH included advanced liver disease and large-volume ascites. Pre paracentesis IAP was higher in ACLF patients (22 vs. 18 mm Hg). Post-paracentesis IAP was also higher in ACLF patients (14 vs. 8 mm Hg, P = .007). The 3-month mortality rate was 50%, with worse survival in ACLF patients (24 vs. 76.9 days, P = .002). Pre-paracentesis IAP was signifi cantly higher in patients who died (22 vs. 18 mm Hg, P = .034), and survival was worse in those with IAP #18.5 mm Hg (P = .026). Conclusion: Intra-abdominal pressure is elevated in cirrhosis patients with grade 3 ascites. Despite similar paracentesis volumes, IAP remained higher in the ACLF group. Intra-abdominal pressure #18.5 mm Hg is associated with significantly reduced survival, indicating that IAH accelerates short-term mortality in these patients. Cite this article as: Mutlu U, Genc Ulucecen S, Iliaz R, et al. Intra-abdominal hypertension and its prognostic impact on mortality in cirrhotic patients with ascites: The role of paracentesis. Turk J Gastroenterol. 2025;36(6):390-397.